2023
DOI: 10.1002/anie.202310066
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Dearomative [2π+2σ] Cycloadditions of Indoles with Bicyclobutanes: Access to Indoline Fused Bicyclo[2.1.1]hexanes**

Lei Tang,
Yuanjiu Xiao,
Feng Wu
et al.

Abstract: Bicyclo[2.1.1]hexanes (BCHs) are becoming ever more important in drug design and development as bridged scaffolds that provide underexplored chemical space, but are difficult to access. Here a silver‐catalyzed dearomative [2π+2σ] cycloaddition strategy for the synthesis of indoline fused BCHs from N‐unprotected indoles and bicyclobutane precursors is described. The strain‐release dearomative cycloaddition operates under mild conditions, tolerating a wide range of functional groups. It is capable of forming BCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Feng and co‐workers later developed a complementary cycloaddition reaction between N‐ H indoles 146 and 1,3‐disubstituted BCBs 147 using silver(I) triflate (AgOTf) as the catalyst (Scheme 23). [49] The authors demonstrated that a wide range of 2‐substituted indoles and BCBs provided BCH products 149 – 152 in up to 99 % yield. Interestingly, the regioselectivity was inverse of what was observed by Deng as the 2‐position of the indole ring was nucleophilic under these conditions instead of the 3‐position.…”
Section: Polar Cycloadditions To Construct Bchsmentioning
confidence: 99%
“…Feng and co‐workers later developed a complementary cycloaddition reaction between N‐ H indoles 146 and 1,3‐disubstituted BCBs 147 using silver(I) triflate (AgOTf) as the catalyst (Scheme 23). [49] The authors demonstrated that a wide range of 2‐substituted indoles and BCBs provided BCH products 149 – 152 in up to 99 % yield. Interestingly, the regioselectivity was inverse of what was observed by Deng as the 2‐position of the indole ring was nucleophilic under these conditions instead of the 3‐position.…”
Section: Polar Cycloadditions To Construct Bchsmentioning
confidence: 99%
“…Soon after, different synthetic strategies to cleave the strained central C–C bond of BCBs and cyclize with alkenes have been demonstrated by the Brown, Procter, Li, and Wang groups independently. Probably, due to the polarity mismatching effect, the electron-rich character of enamines or enamides could hardly engage with alkyl radicals derived from BCBs …”
mentioning
confidence: 99%
“…Apart from these thermally induced conversions, the seminal contributions of Glorius [11] and Brown [12] in the realm of radical BCB-alkene cycloadditions, facilitated by triplet energy transfer, led to the expeditious advancement of radical [2π + 2σ] cycloadditions between BCBs and alkenes (ketones) over the past two years, providing a copious array of enticing (oxa)-BCHs. [13] Furthermore, the employment of Lewis acid catalysis for the [2π + 2σ] cycloadditions involving BCBs has also been substantiated as a potent strategy for the assembly of (hetero)BCHs, as described by Leitch, [14] Glorius, [15] Studer, [16] Deng, [17] and Feng [18] respectively (Scheme 1b). Despite extensive preceding studies, access to bicyclo[3.1.1]heptanes (BCHeps), which function as meta-substituted arene bioisosteres, via cycloadditions of BCBs remains scarce.…”
mentioning
confidence: 99%
“…Notably, nitrones have been successfully involved in a strain-release driven reaction with housane at high temperatures, which was developed by Tanner and Jessing, [24] providing oxaza-bicyclo[3.2.1]octanes. We hypothesize that nitrones could trap the BCBs, serving as dipolarophiles upon activation by Lewis acid, [14][15][16][17][18] and afford a series of structurally novel and biologically interesting 2-oxa-3-azaBCHep skeletons (Scheme 2). According to the literature, BCBs are prone to isomerize upon Lewis acid activation to cyclobutenes.…”
mentioning
confidence: 99%